A kind of magnesium aluminum spinel transparent ceramic with high optical quality and preparation method thereof

By using yttrium aluminum compound as sintering additives, combined with ball milling, calcining, molding and thermal isostatic sintering processes, the grain coarsening and densification unevenness in the existing magnesium aluminum spinel transparent ceramic sintering additives has been solved. , the preparation of magnesium aluminum spinel transparent ceramics with high optical quality and mechanical properties has been achieved.

CN117658617BActive Publication Date: 2025-02-18SHANGHAI INST OF CERAMIC CHEM & TECH CHINESE ACAD OF SCI
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311370006.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-10-20
Publication Date
2025-02-18
Estimated Expiration
2043-10-20

AI Technical Summary

Technical Problem

The sintering aids of existing magnesium-aluminum spinel transparent ceramics such as LiF and CaO have problems with grain coarsing, uneven densification and optical properties, and lack more suitable alternatives.

Method used

Using yttrium aluminum compound as a sintering aid, the raw material powder is obtained by mixing and calcining the phase-forming magnesium aluminum spinel powder with yttrium aluminum compound, followed by molding and thermal isostatic sintering to prepare magnesium of high optical quality. Aluminum spinel transparent ceramic.

Benefits of technology

The high densification rate and excellent optical quality of magnesium-aluminum spinel transparent ceramics have been achieved, and they have good mechanical properties, and their transmittance and bending strength have been significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117658617B_ABST
    Figure CN117658617B_ABST
Patent Text Reader

Abstract

The present invention relates to a magnesium-aluminum spinel transparent ceramic with high optical quality and a preparation method thereof, and belongs to the technical field of ceramic materials. The preparation method comprises: step (1): mixing a phased magnesium-aluminum spinel powder with a sintering aid by ball milling and calcining to obtain a raw material powder; preferably, the sintering aid is a yttrium aluminum compound, preferably YAG (Y3Al5O 12 ), YAM (Y4Al2O9), YAP (YAlO3); step (2): forming the obtained raw material powder into a green blank; step (3): calcining and pressureless sintering the green blank to obtain a pre-burned body; step (4): hot isostatic pressing the pre-burned body to obtain a magnesium-aluminum spinel transparent ceramic with high optical quality. The method has a simple preparation process and strong repeatability. The obtained magnesium-aluminum spinel transparent ceramic has excellent optical quality in the visible-near infrared band and good mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to magnesium-aluminum spinel transparent ceramics with high optical quality and a preparation method thereof, belonging to the technical field of ceramic materials. Background Art

[0002] Magnesium aluminum spinel transparent ceramics are a kind of ceramic material with special optical properties. It has the advantages of high transparency, high hardness, high temperature resistance and chemical stability. Magnesium aluminum spinel transparent ceramics are widely used in optics, electronics, military and aviation fields, so they have attracted much attention.

[0003] In the 1960s, researchers first attempted to prepare magnesium-aluminum spinel ceramics using high-temperature solid-phase reaction sintering. Since then, magnesium-aluminum spinel transparent ceramics have been widely used in the optical and military fields. Its high transparency, high hardness and high temperature resistance make it an ideal material for laser systems, infrared optical systems and military equipment. With the advancement of materials science and engineering technology, the preparation process of magnesium-aluminum spinel transparent ceramics has gradually become more precise and controllable. Continuous improvements in technologies such as high-temperature sintering, powder metallurgy and ceramic forming have provided more options and possibilities for the preparation of magnesium-aluminum spinel transparent ceramics. In the past decade, research on magnesium-aluminum spinel transparent ceramics has made great progress, and the preparation of high-quality magnesium-aluminum spinel transparent ceramics has been successfully achieved.

[0004] Sintering aid is one of the key factors in preparing high-quality magnesium-aluminum spinel transparent ceramics. In recent decades, sintering aid has been one of the focuses of researchers. At present, researchers have conducted in-depth research on a variety of sintering aids including LiF, CaO, CaCO3 and La2O3.

[0005] LiF is the most commonly used sintering aid for commercial magnesium-aluminum spinel transparent ceramics. It can promote the densification of materials by liquid phase sintering and reduce the sintering temperature. In addition, lithium and fluorine can replace magnesium and oxygen sites, thereby producing certain defects and increasing the diffusion rate. LiF can also act as a scavenger because fluorine reacts with impurities generated in the raw material powder or during processing (such as carbon in HP or SPS graphite molds) to form volatile compounds. However, LiF as a sintering aid for magnesium-aluminum spinel transparent ceramics also has some disadvantages. First, LiF may cause grain coarsening, thereby hindering the densification process of the material. In addition, the carbon contamination introduced from the graphite mold needs to be accurately controlled. Secondly, LiF vaporizes above 1000°C, and uneven LiF volatilization will cause local differences in the sample during the sintering process, thereby reducing the microstructural uniformity and optical properties of the transparent ceramic sample.

[0006] CaO is also a commonly used sintering aid in the preparation of magnesium-aluminum spinel transparent ceramics. Studies have shown that CaO as a sintering aid can react with magnesium-aluminum spinel to form a low-melting calcium aluminate phase, which can effectively reduce the sintering temperature and significantly improve the optical transmittance of the sample, especially in the ultraviolet band. However, at higher sintering temperatures, calcium aluminate will precipitate and form a second phase, which will affect the microstructure of the final sample.

[0007] Although LiF and CaO have some shortcomings as sintering aids, no more suitable substitutes have been found so far. Therefore, they are still widely used in the preparation of magnesium-aluminum spinel transparent ceramics. However, it is urgent to explore new sintering aid systems to replace LiF and CaO.

[0008] New sintering aids need to improve the densification rate of magnesium-aluminum spinel ceramics while ensuring their optical quality. When looking for a new sintering aid system, the following factors need to be considered: First, the sintering effect. The new aid should be able to effectively promote the densification process of magnesium-aluminum spinel ceramic samples and promote the elimination of pores. Secondly, the introduction of new aids should not excessively affect the mechanical properties of the sample. Finally, new aids also need to consider factors such as cost and availability. Therefore, future research should be committed to finding and developing new sintering aid systems suitable for the preparation of magnesium-aluminum spinel transparent ceramics to improve preparation efficiency and optical quality. This will help promote further development and application in this field. Summary of the invention

[0009] In view of the above problems, the purpose of the present invention is to provide a magnesium-aluminum spinel transparent ceramic with high optical quality and a preparation method thereof. The preparation process of the method is simple and highly repeatable, and the obtained magnesium-aluminum spinel transparent ceramic has excellent optical quality in the visible-near infrared band and good mechanical properties.

[0010] In a first aspect, the present invention provides a method for preparing a magnesium-aluminum spinel transparent ceramic with high optical quality. The preparation method comprises:

[0011] Step (1): ball-milling and mixing the phase-forming magnesium aluminum spinel powder and the sintering aid, and calcining to obtain a raw material powder; preferably, the sintering aid is a yttrium aluminum compound, preferably YAG (Y3Al5O 12 ), a mixture of one or more of YAM (Y4Al2O9), and YAP (YAlO3);

[0012] Step (2): forming the obtained raw material powder into a green billet;

[0013] Step (3): calcining and pressureless sintering the green blank to obtain a pre-burnt body;

[0014] Step (4): The pre-fired body is subjected to hot isostatic pressing to obtain a magnesium-aluminum spinel transparent ceramic with high optical quality.

[0015] Compared with Y2O3 additives and yttrium-containing fluoride additives (such as YOF), yttrium aluminum compounds will not take away too much aluminum from magnesium aluminum spinel, and can better control the aluminum-magnesium ratio of magnesium aluminum spinel transparent ceramics. In addition, the liquid phase sintering effect of YOF will promote the sintering densification to a certain extent, and it is more likely to cause the formation of intracrystalline pores, thereby affecting the transmittance and mechanical properties of the sample. Yttrium aluminum compounds will not affect the densification process too much during the sintering process, and the pinning effect at the grain boundary is conducive to the removal of nanopores along the grain boundary.

[0016] Preferably, the sintering aid is added in an amount of 0.005wt% to 0.2wt% of the phase-forming magnesium aluminate spinel powder, preferably 0.005wt% to 0.08wt%.

[0017] Preferably, the purity of the phase-forming magnesium aluminum spinel powder is ≥99.8%, and the primary particle size is 20nm-200nm; the purity of the sintering aid is ≥99.7%, and the primary particle size is 20nm-3000nm.

[0018] Preferably, in step (1), the calcination is carried out at 500-900° C. in an air atmosphere for 4-12 hours.

[0019] Preferably, in step (2), the forming is dry pressing and / or cold isostatic pressing; preferably, dry pressing is performed first and then cold isostatic pressing; the pressure of the dry pressing is 5 to 30 MPa and the time is 1 to 3 minutes, and the pressure of the cold isostatic pressing is 150 to 250 MPa and the time is 5 to 20 minutes.

[0020] Preferably, the calcined body is a calcined body with open pores and closed pores, and has a relative density of 90 to 99%.

[0021] Preferably, in step (3), the calcination is carried out at 600-900°C in an air atmosphere for 4-10 hours; the pressureless sintering temperature is 1300-1600°C, the pressureless sintering time is 1-10 hours, and the atmosphere is air atmosphere, argon atmosphere or vacuum.

[0022] Preferably, in step (4), the hot isostatic pressing sintering temperature is 1400°C to 1900°C, the hot isostatic pressing sintering time is 1 to 6 hours, the atmosphere is an inert atmosphere, and the pressure is 100 to 250 MPa; preferably, the inert atmosphere is nitrogen and / or argon.

[0023] In a second aspect, the present invention provides a magnesium-aluminum spinel transparent ceramic with high optical quality. The ceramic is obtained by the method for preparing a magnesium-aluminum spinel transparent ceramic with high optical quality described in any one of the above items. The magnesium-aluminum spinel transparent ceramic with high optical quality comprises a phase-forming magnesium-aluminum spinel matrix and a YAG phase uniformly distributed in the phase-forming magnesium-aluminum spinel matrix, and the YAG phase accounts for 0.005wt% to 0.2wt% of the phase-forming magnesium-aluminum spinel matrix, preferably 0.005wt% to 0.08wt%.

[0024] Preferably, when the thickness of the high optical quality magnesium aluminum spinel transparent ceramic is ≥4 mm, the linear transmittance in the wavelength range of 400-2500 nm is ≥79.5%. In some technical solutions, when the thickness of the high optical quality magnesium aluminum spinel transparent ceramic is ≥4 mm, the linear transmittance in the wavelength range of 400-2500 nm can be as high as 84.0%. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a photo of the magnesium aluminum spinel transparent ceramic sample prepared in Example 1 after double-sided polishing.

[0026] Figure 2 This is a linear transmittance curve of the magnesium aluminum spinel transparent ceramic sample prepared in Example 1.

[0027] Figure 3 These are photos of the magnesium-aluminum spinel transparent ceramic samples prepared in Example 2 with different contents of YAG sintering aid added.

[0028] Figure 4 This is a comparison chart of the linear transmittance curves of the magnesium-aluminum spinel transparent ceramic samples prepared in Example 2 and added with different contents of YAG sintering aid.

[0029] Figure 5 This is a comparison chart of the linear transmittance curves of the magnesium-aluminum spinel transparent ceramic samples prepared in Example 3 and added with different contents of YAG sintering aid.

[0030] Figure 6 This is a photo of the magnesium aluminum spinel ceramic sample prepared in Comparative Example 1 after double-sided polishing.

[0031] Figure 7 This is a photo of the magnesium aluminum spinel ceramic sample prepared in Comparative Example 2 after double-sided polishing.

[0032] Figure 8 This is a photo of the magnesium aluminum spinel ceramic sample prepared in Comparative Example 3 after double-sided polishing.

[0033] Fig. 9 The shrinkage curves of the samples of Comparative Examples 2 and 3 are shown in FIG. DETAILED DESCRIPTION

[0034] The present invention is further described by the following embodiments. It should be understood that the following embodiments are only used to illustrate the present invention, but not to limit the present invention. In the absence of special instructions, each percentage content refers to the percentage content by mass.

[0035] The present invention uses magnesium aluminum spinel nanopowder as raw material, promotes densification and the elimination of pores by adding a sintering aid with a special structure, and adopts a pressureless sintering combined with hot isostatic pressing sintering to prepare magnesium aluminum spinel transparent ceramics with high optical quality. The method of the present invention mainly includes three steps: preparation of raw material powder, molding and sintering densification.

[0036] Preparation of raw material powder: The phase-forming magnesium aluminum spinel powder and the sintering aid are ball-milled and calcined to obtain the raw material powder.

[0037] The phase-forming magnesium aluminum spinel powder can be high-purity commercial magnesium aluminum spinel nanopowder with a purity of ≥99.8% and a primary particle size of 20nm-200nm. The purity of the sintering aid powder can be ≥99.7% and a primary particle size of 20nm-3000nm, preferably 20nm-1000nm.

[0038] The sintering aid may be a single aid or multiple aids. The sintering aid is a yttrium aluminum compound. As an example, the sintering aid includes but is not limited to YAM (Y4Al2O9), YAP (YAlO3), YAG (Y3Al5O 12 ) and other yttrium-containing aluminum compounds or a mixture of one or more thereof.

[0039] In some technical solutions, the magnesium-aluminum ratio of the phase-forming magnesium-aluminum spinel powder is 1 to 1.5.

[0040] Compared with Y2O3 and YOF additives, yttrium aluminum compounds will not take away too much aluminum from magnesium aluminate spinel, thus affecting the performance of magnesium aluminate spinel ceramics. For example, when magnesium aluminate spinel powder with an aluminum-magnesium ratio of 1.5 is used, Y2O3 as a sintering aid can promote densification, effectively prevent the precipitation of the metastable magnesium aluminate spinel second phase, and significantly improve the overall transmittance of magnesium aluminate spinel ceramic samples, but there is no obvious improvement in the mechanical properties of the samples. In other words, the Y2O3 additive cannot take into account the improvement of both optical and mechanical properties at the same time. The reason is probably that the Y2O3 additive will react with spinel and change the local aluminum-magnesium ratio, thereby affecting the performance of transparent ceramics. In other words, although Y2O3 can generate compounds with Al2O3 from the magnesium aluminate spinel matrix to play a role in grain boundary pinning and inhibit grain growth. However, this will take away Al2O3 from the magnesium aluminate spinel matrix and affect the comprehensive performance of the sample.

[0041] The use of a mixture of Y2O3 and Al2O3 as a sintering aid also fails to achieve the technical effects of the present application. This is because: First, the main reason why the Y2O3 additive cannot take into account both the optical and mechanical properties of magnesium-aluminum spinel transparent ceramics is that it may react with nearby spinels to capture the Al element and cause local unevenness. The uneven mixing of Y2O3 and Al2O3 is likely to further aggravate this situation. Second, solid-phase reactions will cause volume expansion and contraction. For example, the reaction of magnesium oxide and aluminum oxide to form spinel will produce a volume expansion of about 5-8%. This is not conducive to the elimination of pores.

[0042] Similarly, the liquid phase sintering effect of YOF will promote the sintering densification to a certain extent, leading to grain growth and the generation of intracrystalline pores, which in turn affects the transmittance and mechanical properties of the sample. Yttrium aluminum compounds will not affect the densification process too much during the sintering process, and the pinning effect at the grain boundary is conducive to the removal of nanopores along the grain boundary. The experiment found that at the same mass percentage addition amount (0.01wt.%), the improvement of optical properties by YAG additives is significantly better than that of YOF additives.

[0043] Taking the total mass of the phase-forming magnesium aluminum spinel powder as 100%, the mass concentration of the sintering aid may be 0.005wt% to 0.2wt%, preferably 0.005wt% to 0.08wt%, and more preferably 0.005wt% to 0.05wt%.

[0044] When the sintering aid is YAG, the added amount is preferably 0.01 wt% to 0.03 wt%.

[0045] Specifically, the phase-forming magnesium aluminum spinel powder and the sintering aid are ball-milled and mixed, and then dried, sieved, and calcined to obtain a raw material powder. In some embodiments, the phase-forming magnesium aluminum spinel powder and the sintering aid are weighed, and alumina balls are used as ball milling media, and anhydrous ethanol is used as a dispersion medium. The phase-forming magnesium aluminum spinel powder and the sintering aid are ball-milled with alumina balls and anhydrous ethanol to ensure that they are evenly mixed.

[0046] The phase-forming magnesium aluminum spinel powder and the sintering aid can be added to alumina balls and anhydrous ethanol, and ball milled (grinded) using a ball mill to obtain a mixture. The ball milling time and ball milling speed need to be properly controlled to obtain the desired uniformity. The ball milling can be carried out at a speed of 250 rpm for 3 to 12 hours.

[0047] After the ball milling is completed, the mixture is dried. The drying condition is to dry at 50-80°C for 24-48 hours. Screening is performed through a sieve to remove unnecessary particles and impurities. The sieve used for screening is a 80-200 mesh sieve; preferably, the sieve is a 100 mesh sieve. The calcination is to keep warm at 500-900°C in a muffle furnace for 4-12 hours. In this way, a raw material powder that meets the requirements is obtained for the subsequent sintering process.

[0048] Molding of raw powder. The raw powder is placed in a molding mold and a certain pressure is applied for compression molding. A ceramic blank of the desired shape and size can be obtained by molding. The raw powder can be pressed by dry pressing and / or cold isostatic pressing to obtain a blank. For example, the raw powder is directly subjected to cold isostatic pressing to form a blank. The pressure range of cold isostatic pressing is 150-250 MPa, and the processing time is 5-20 minutes. Preferably, dry pressing is performed first, and then cold isostatic pressing is performed. As a specific example, the calcined raw powder is placed in a mold, a pressure of 5-30 MPa is used, and the dry pressed blank is obtained by maintaining the pressure for 1-6 minutes (preferably 1-3 minutes); then the dry pressed blank is subjected to cold isostatic pressing, and the pressure range of cold isostatic pressing is 150-250 MPa, and the processing time is 5-20 minutes. The dry pressed blank or the raw powder that has been calcined and removed impurities can be vacuum packaged before cold isostatic pressing.

[0049] Sintering densification of the biscuit. After the formed biscuit is calcined, pressureless sintered and hot isostatic pressing (also known as hot isostatic pressing), the high optical quality magnesium aluminum spinel transparent ceramic is obtained. The specific steps are: calcining the formed ceramic biscuit. Calcination is usually carried out at a lower temperature. The purpose of calcination is to remove organic matter introduced during the forming process. The calcination temperature and calcination time need to be properly controlled to ensure that the organic matter inside the ceramic body is fully burned out. Calcination can be carried out in a muffle furnace. As an example, the calcination temperature is 600-900°C and the calcination time is 4-10 hours. The calcined ceramic biscuit is then subjected to pressureless sintering (also known as pressureless pre-firing) to obtain a pre-fired body. The temperature of the pressureless pre-firing is 1300-1600°C and the time is 1-10 hours. The pressureless sintering includes air pre-firing or vacuum pre-firing. That is, the atmosphere of pressureless sintering is air atmosphere or vacuum. The calcined body is a calcined body with open pores and closed pores, and the relative density is 90-99%. Generally, a better hot isostatic pressing sintering effect can be obtained when the relative density is about 95%. The calcined body is subjected to hot isostatic pressing to obtain high-quality magnesium aluminum spinel transparent ceramics. The hot isostatic pressing temperature is 1400-1900°C, the time is 1-6 hours, the atmosphere used is an inert atmosphere such as nitrogen and / or argon, and the pressure is 100-250MPa.

[0050] As a preferred technical solution, the temperature of the pressureless pre-sintering is 1450-1600°C, and the amount of the sintering aid YAG added is 0.01wt%-0.03wt%. At this time, when the thickness of the magnesium aluminum spinel transparent ceramic is ≥4mm, the linear transmittance in the wavelength range of 400-2500nm is ≥82%, for example, it can reach 82%-84%.

[0051] High-quality magnesium-aluminum spinel transparent ceramics can be polished. For example, double-sided polishing can be performed on samples after hot isostatic pressing. After double-sided polishing, magnesium-aluminum spinel transparent ceramics have higher density, strength and optical transparency.

[0052] The magnesium aluminum spinel transparent ceramic obtained by the above method includes a phase magnesium aluminum spinel matrix and a YAG phase uniformly distributed in the phase magnesium aluminum spinel matrix. The YAG phase accounts for 0.005wt% to 0.2wt% of the phase magnesium aluminum spinel matrix, preferably 0.005wt% to 0.08wt%. That is to say, whether the sintering aid is YAG (Y3Al5O 12 ), YAM (Y4Al2O9), YAP (YAlO3), or a precursor that can react with the phase-forming magnesium aluminum spinel powder to form a YAG phase, or a mixture of the two. The final concentration of the YAG phase in the magnesium aluminum spinel transparent ceramic (relative to the magnesium aluminum spinel matrix) is preferably 0.005wt% to 0.2wt%. Otherwise, too much second phase will seriously affect the optical and mechanical properties of the sample.

[0053] When the sintering aid is at least one of the fluorides or fluoride oxides containing Y, La, and Lu, the magnesium aluminate spinel powder can certainly generate YAG phase and / or lanthanum aluminum compound and / or lutetium aluminum compound with the sintering aid. However, in the process of generating the corresponding second phase, the sintering aid will react with the spinel to capture the Al element, thereby affecting the performance of the magnesium aluminate spinel.

[0054] The magnesium-aluminum spinel transparent ceramic has an average grain size of 1 to 5 μm and a bending strength of more than 330 MPa (eg, 330 to 350 MPa).

[0055] When the thickness of the magnesium aluminum spinel transparent ceramic is greater than or equal to 4 mm, the linear transmittance in the visible-near infrared light band of 400 nm to 2500 nm is greater than or equal to 79.5%.

[0056] The advantages of the present invention are: 1) Compared with the existing preparation technology of magnesium-aluminum spinel transparent ceramics, the sintering aid selected by the present invention can effectively promote the sintering and densification of magnesium-aluminum spinel ceramics when added in an appropriate amount, and the grain size of the obtained magnesium-aluminum spinel transparent ceramics is uniform and there are no obvious pores. The sample has high optical quality and mechanical properties, and the transmittance at 400nm can reach 84.0% (sample thickness ≥ 4mm), the bending strength can reach 347MPa, and the Vickers hardness can reach 13.8GPa. Compared with the sample without adding additives, the transmittance and mechanical properties are significantly improved. 2) The preparation method of the present invention adopts a process of pressureless sintering combined with hot isostatic pressing treatment. The process is relatively simple, and the required pre-firing temperature and hot isostatic pressing temperature are both low. The required amount of sintering aid is also low, and it can be mass-produced at a lower cost under existing technical conditions.

[0057] The present invention is described in detail with reference to a plurality of specific embodiments below. Similarly, it should be understood that the following embodiments are only used to further illustrate the present invention, but not to limit the present invention. The non-essential improvements or adjustments made by relevant technical personnel in the field according to the content of the present invention all belong to the protection scope of the present invention. The specific process parameters etc. in the following examples are also only an example in a suitable range, that is, relevant technical personnel in the field can select in a suitable range through the content of the present invention, and are not limited to the specific numerical values ​​in the following examples.

[0058] Example 1

[0059] (1) Raw material powder processing: The total mass of the phased magnesium aluminum spinel powder is calculated as 100wt%, and 0.01wt% YAG additive is added. Anhydrous ethanol is used as the dispersion medium, and high-purity alumina balls are used as the ball milling medium. The mass ratio of ball milling medium: anhydrous ethanol: raw material is 1:2.5:5. Use a planetary ball mill for ball milling, the ball milling speed is 250 rpm, and the ball milling time is 12 hours. The ball-milled slurry is placed in a 65℃ oven and dried for 12 hours. The dried powder is sieved through a 100-mesh sieve. Finally, in order to remove organic impurities introduced during ball milling and sieving, the sieved powder is placed in a muffle furnace and calcined at 800℃ in an air atmosphere for 6 hours.

[0060] (2) Molding: The calcined raw material powder is molded by dry pressing and cold isostatic pressing to obtain a magnesium aluminum spinel ceramic blank, wherein the dry pressing pressure is 10 MPa and the pressure is maintained for 2 minutes, and the cold isostatic pressing pressure is 200 MPa and the pressure is maintained for 3 minutes.

[0061] (3) Sintering densification: To remove organic impurities introduced during the molding process, the formed green body was first calcined in a muffle furnace at 800°C in air atmosphere for 6 hours. Then, after pressureless pre-sintering at 1460°C in air atmosphere for 6 hours, a pre-sintered body with a relative density of 95.22% and closed pores was obtained. The pre-sintered body was hot isostatically pressed at 200 MPa pressure and 1600°C in argon atmosphere for 3 hours to obtain a magnesium-aluminum spinel transparent ceramic sample.

[0062] Figure 1 This is a picture of the magnesium-aluminum spinel transparent ceramic obtained in Example 1 after double-sided polishing. The sample was double-sided polished to a thickness of 4 mm. It can be seen that the prepared magnesium-aluminum spinel transparent ceramic has high transparency.

[0063] Figure 2 The straight-line transmittance graph of the magnesium-aluminum spinel transparent ceramic prepared in Example 1. The sample was double-sided polished to a thickness of 4 mm. The transmittance of the magnesium-aluminum spinel transparent ceramic with 0.01 wt.% YAG added was 84.0% at 400 nm and 87.0% at 1100 nm, which is close to the theoretical transmittance in this band.

[0064] Example 2

[0065] The preparation process is similar to that of Example 1, except that 0.005wt%, 0.03wt% and 0.1wt% YAG are added as sintering aids, respectively, the pre-sintering temperature of the green billet after forming is 1450°C, and the hot isostatic pressing temperature is 1500°C.

[0066] Figure 3 This is a picture of the double-sided polished magnesium aluminum spinel transparent ceramic obtained in Example 2. All samples were double-sided polished to a thickness of 4 mm.

[0067] Figure 4 The linear transmittance curve of the magnesium aluminum spinel transparent ceramic sample prepared in Example 2. All samples were double-sided polished to a thickness of 4 mm. Figure 4 It can be seen that the samples all have high transmittance, and the transmittances at 400 nm are 79.5%, 80.8% and 79.5% respectively.

[0068] Example 3

[0069] The preparation process is similar to that of Example 1, except that 0, 0.01wt%, 0.03wt% and 0.05wt% YAG are added as a sintering aid, respectively, and the pre-sintering temperature of the green billet after forming is 1500°C.

[0070] Figure 5 The linear transmittance curve of the magnesium aluminum spinel transparent ceramic obtained in Example 3. All samples were double-sided polished to a thickness of 4 mm. Figure 5It can be seen that the transmittance of the sample decreases significantly with the increase of the amount of YAG added. Among them, the transmittance of the magnesium aluminum spinel transparent ceramics with 0, 0.01wt% and 0.03wt% YAG additives at 400nm is 80.3%, 83.8% and 82.8% respectively. When the pre-sintering temperature is 1500℃, the optimal addition amount of YAG additive is 0.01wt%, and its transmittance is significantly higher than that of the sample without sintering additives, indicating that a small amount of YAG can significantly improve the optical quality of the sample.

[0071] Comparative Example 1

[0072] The preparation process of this comparative example refers to Example 1. The main difference is that in step (1), no sintering aid is added.

[0073] Figure 6 This is a photo of the magnesium-aluminum spinel ceramic sample prepared in Comparative Example 1 after double-sided polishing. The sample was double-sided polished to a thickness of 4 mm. It can be seen from the figure that the sample is an opaque magnesium-aluminum spinel ceramic.

[0074] Comparative Example 2

[0075] The preparation process of this comparative example refers to Example 2. The main difference is that in step (1), no sintering aid is added.

[0076] Figure 7 This is a photo of the magnesium-aluminum spinel ceramic sample prepared in Comparative Example 2 after double-sided polishing. The sample was double-sided polished to a thickness of 4 mm. It can be seen from the figure that the sample is an opaque magnesium-aluminum spinel ceramic.

[0077] Compared with Example 2, it is found that at a pre-sintering temperature of 1450°C, the sample without additives becomes opaque after hot isostatic pressing at 1500°C.

[0078] Comparative Example 3

[0079] The preparation process of this comparative example refers to Example 3. The main difference is that in step (1), 0.1 wt% YAG is added as a sintering aid.

[0080] Figure 8 This is a photo of the magnesium aluminum spinel ceramic sample prepared in Comparative Example 3 after double-sided polishing. The sample was double-sided polished to a thickness of 4 mm. It can be seen from the figure that the transmittance of the sample is poor.

[0081] Fig. 9 is the shrinkage curve of the calcined body in Comparative Example 2 and Comparative Example 3. Fig. 9The shrinkage curve of the sample with 0.1wt% YAG additive is basically the same as that of the sample without additive. Therefore, directly using YAG as an additive has a very low impact on the densification rate. Therefore, YAG as an additive will not affect other properties (such as mechanical properties) while improving a certain property (such as optical properties) like Y2O3 additives.

[0082] The three-point bending strength of transparent ceramic samples was tested using a universal testing machine (Instron-5566 from INSTRON, UK). The samples needed to be processed into a size of 3mm×4mm×36mm, and the sample surface was polished. At the same time, the long edges of the samples were chamfered at 45° to eliminate stress defects on the sample surface and edges caused by processing. At least 10 test strips were selected for each group of samples, and the final test result was the average of at least 10 data. The Vickers hardness of the sample was tested using a Vickers hardness tester (Tukon2100B, INSTRON, UK) (indentation method, 1kg load), and the hardness values ​​of five different areas were measured and the average value was calculated.

[0083] Table 1 Bending strength and Vickers hardness of the magnesium aluminum spinel transparent ceramics prepared in Example 3 and Comparative Example 3

[0084] 0wt.% 0.01wt.% 0.03wt.% 0.1wt.% Bending strength / MPa 313±63 347±54 333±22 210±32 Vickers hardness / GPa 13.4±0.4 13.8±0.5 13.8±0.7 13.4±0.3

[0085] It can be seen from Table 1 that by adding an appropriate amount of sintering aid YAG, the flexural strength of the magnesium-aluminum spinel transparent ceramic is significantly improved and the Vickers hardness is slightly enhanced.

Claims

1. A method for preparing magnesium aluminum spinel transparent ceramics with high optical quality, characterized in that: The preparation method comprises: Step (1): ball-milling and mixing the phase-forming magnesium aluminum spinel powder and the sintering aid, and calcining to obtain a raw material powder; the sintering aid is a yttrium aluminum compound, such as YAG (Y3Al5O 12 ), YAM (Y4Al2O9), YAP (YAlO3) or a mixture of one or more thereof; the sintering aid is added in an amount of 0.005 wt% to 0.08 wt% of the phase-forming magnesium aluminum spinel powder; Step (2): forming the obtained raw material powder into a green billet; Step (3): calcining and pressureless sintering the green body to obtain a pre-burnt body; Step (4): sintering the pre-calcined body by hot isostatic pressing to obtain a magnesium-aluminum spinel transparent ceramic with high optical quality; The magnesium aluminum spinel transparent ceramic with high optical quality comprises a phased magnesium aluminum spinel matrix and a YAG phase uniformly distributed in the phased magnesium aluminum spinel matrix, wherein the YAG phase accounts for 0.005 wt% to 0.08 wt% of the phased magnesium aluminum spinel matrix.

2. The preparation method according to claim 1, characterized in that The purity of the phase-forming magnesium aluminum spinel powder is ≥99.8%, and the primary particle size is 20nm~200nm; the purity of the sintering aid is ≥99.7%, and the primary particle size is 20nm~3000nm.

3. The preparation method according to claim 1, characterized in that: In step (1), the calcination is carried out in an air atmosphere at 500-900° C. for 4-12 hours.

4. The preparation method according to claim 1, characterized in that: In step (2), the forming is dry pressing and / or cold isostatic pressing.

5. The preparation method according to claim 4, characterized in that: The forming process is dry pressing first and then cold isostatic pressing.

6. The preparation method according to claim 4, characterized in that The pressure of the dry pressing molding is 5-30 MPa, and the time is 1-3 minutes; the pressure of the cold isostatic pressing molding is 150-250 MPa, and the time is 5-20 minutes.

7. The preparation method according to claim 1, characterized in that: The calcined body is a calcined body with open pores and closed pores, and has a relative density of 90-99%.

8. The preparation method according to claim 1, characterized in that: In step (3), the calcination is carried out in an air atmosphere at 600-900°C for 4-10 hours; the pressureless sintering temperature is 1300-1600°C, the pressureless sintering time is 1-10 hours, and the atmosphere is air atmosphere, argon atmosphere or vacuum.

9. The preparation method according to claim 1, characterized in that: In step (4), the hot isostatic pressing sintering temperature is 1400° C. to 1900° C., the hot isostatic pressing sintering time is 1 to 6 hours, the atmosphere is an inert atmosphere, and the pressure is 100 to 250 MPa.

10. The preparation method according to claim 9, characterized in that: The inert atmosphere is nitrogen and / or argon.

11. The preparation method according to claim 1, characterized in that When the thickness of the magnesium-aluminum spinel transparent ceramic with high optical quality is ≥4 mm, the linear transmittance in the wavelength range of 400-2500 nm is ≥79.5%.

Citation Information

Patent Citations

  • Magnesium aluminate spinel transparent ceramic and preparation method thereof

    CN116553922A